2017
DOI: 10.1504/ijbpm.2017.10001261
|View full text |Cite
|
Sign up to set email alerts
|

Workplace context and its effect on individual competencies and performance in work teams

Abstract: Abstract:The purpose of this study was to understand the effect of workplace context on competencies and performance in work (project) teams. This study was conducted at seven technology-based companies in Hong Kong and China. The results of the study provide companies with important knowledge on how to encourage the right competencies to achieve high performance in a workplace. This paper attempts to propose a holistic approach on improving individual and team performance in companies. The empirical evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A successful internship experience for nursing interns depends on interaction with both hospital staff and their educational institution. A detached or disassociated relationship between the institutions where the clinical training and planning are taking place can negatively affect nursing interns' transition to independent professional nurses (Eick, Williamson & Heath, 2012;Leufer & Cleary-Holdforth, 2020;Rozhkov, 2015;Shaban et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A successful internship experience for nursing interns depends on interaction with both hospital staff and their educational institution. A detached or disassociated relationship between the institutions where the clinical training and planning are taking place can negatively affect nursing interns' transition to independent professional nurses (Eick, Williamson & Heath, 2012;Leufer & Cleary-Holdforth, 2020;Rozhkov, 2015;Shaban et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Hickey revealed a lack of psychomotor skills to perform the required procedures among nursing interns (Hickey, 2009). Context meanwhile includes the physical and social conditions surrounding a nursing intern in which their daily work occurs (Rozhkov, 2015). These physical conditions include the institutional structure and the objects inside it.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the term project organizational environment (project context) is defined as the set of conditions in which a project is implemented (Rozhkov et al 2013). Furthermore, the perception of the project organizational environment is highlighted in two aspects:…”
Section: Project Organizational Environmentmentioning
confidence: 99%
“…Dynamic pricing, also known as the demand pricing, is where a businessman prices an item based on environmental factors such as the hobby of the target consumer, demand at the time of buy, or whether the customer has engaged with an advertising campaign [42]. This requires numerous statistics about how one of kind clients' willingness to pay for a good or provider adjustments throughout a variety of situations, however via machine gaining knowledge of packages, groups like airlines and rideproportion services have successfully implemented dynamic charge optimization strategies to maximize revenue [43]. This can also be utilized by upcoming and current small businesses to minimize loss and enhance more profits.…”
Section: Easier Social Media Monitoringmentioning
confidence: 99%